2009
DOI: 10.1093/europace/eup318
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of paroxysmal atrial tachycardias in patients treated with cardiac resynchronization therapy and continuously monitored by device diagnostics

Abstract: More than 20% of the overall HF patient population treated with CRT suffer PAT episodes. Paroxysmal atrial tachycardia may interfere with response to CRT. Therefore, telemetric data may be relevant to drive the appropriate therapy in each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…It should also be noted that the rate of new-onset AT in MADIT-CRT was somewhat lower (8%) than that in prior CRT studies that enrolled patients with more advanced HF symptoms (in which the reported frequency of new-onset AT was between 10% and 30%) (8,14,15,18). Thus, the present findings regarding reduction in the risk of newonset AT/AF among responders to CRT-D therapy pertain only to patients with asymptomatic or mildly symptomatic LV dysfunction.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It should also be noted that the rate of new-onset AT in MADIT-CRT was somewhat lower (8%) than that in prior CRT studies that enrolled patients with more advanced HF symptoms (in which the reported frequency of new-onset AT was between 10% and 30%) (8,14,15,18). Thus, the present findings regarding reduction in the risk of newonset AT/AF among responders to CRT-D therapy pertain only to patients with asymptomatic or mildly symptomatic LV dysfunction.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have suggested that CRT is associated with favorable reverse remodeling effects on the left atrium (LA), in addition to its well-established effects on the left ventricle (LV), thereby possibly reducing the risk for the development of AT and AF in patients with HF (9,10). Despite this, data on the effect of CRT on the resolution of chronic and prevention of new atrial arrhythmias are conflicting (11)(12)(13)(14)(15), possibly because the majority of prior studies had a nonrandomized or retrospective design and comprised relatively small sample sizes. Furthermore, previous studies were carried out among patients with advanced HF symptoms (NYHA functional class III/IV); however, currently there are no data regarding the effect of CRT on the risk of AT among patients with mild HF symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies analyzed device-stored data to assess the incidence of AF in CRT patients [5,[8][9][10][11][12][13][14][15][16][17]. However, in the great majority of them + p < 0.05 vs. group with AF during follow-up; #79 patients survived the 24-month period: 10 with and 69 without AF history prior to cardiac resynchronization therapy.…”
Section: Discussionmentioning
confidence: 99%
“…New technologies monitor not only device function but also patient physiology including heart rate and rhythm, heart rate variability, activity and thoracic bioimpedance that may help improve the management of heart failure [58][59][60][61][62][63][64][65]. Monitoring of the device function has already been shown to have benefits in terms of early warning of device failure.…”
mentioning
confidence: 99%